PERILAKU SILINDER BETON BERONGGA YANG DIKEKANG DENGAN TULANGAN SPIRAL - Sudarsana, Wayan (Jurnal Ilmiah Teknik Sipil, 2012)
The increase in compressive strength of concrete cylinder confined by spiral reinforcement has been well written in literature. The study of hollow concrete cylinder confined by spiral reinforcement, however, is very limited. Based on this situation, the author has conducted a study in which the increases of compressive strength of hollow concrete cylinder confined by spiral reinforcement were utilized to reduce further the cross sectional area of the concrete that could be reduced without lowering its supporting capacity and the concrete become more economical. The existence of hollow inside the cross section may give significant influence on the behavior of the structural element in the concrete to the withstand compression. The behavior of structural element in withstanding load could be studied through their stress-strain diagrams. The analysis is carried out by comparing those stress-strain diagrams of concrete cylinder that are massive and hollowed, and when those cylinders are either confined or unconfined. Furthermore, the stress-strain behavior of the massive concrete cylinder confined by spiral reinforcement could be predicted by means of equation proposed by Shah et.al (1983) and by Mander et.al (1984). By comparing the results from the laboratories testing and those predicted results from theory, the final conclusion on this concrete behavior could be assessed. The result of this study revealed that hollowed concrete cylinder confined by spiral reinforcement generally more brittle when compared with massive concrete cylinder confined in similar manner. The existence of hollow, however, did not reduce the concrete compressive strength.
Keywords: hollow concrete cylinder, spiral reinforcement, concrete compressive strength